PERAN KELUARGA DALAM MENGEMBANGKAN ASPEK MORAL MELALUI PEMBIASAAN BERKATA MAAF TOLONG DAN TERIMA KASIH PADA AUD - N, Nuraini; Syam, A. Sri Mardiyanti (EDUCHILD (Journal of Early Childhood Education), 2022)
This Study discusses the role of the family in developing moral aspects through thehabit of sorry, please and than you to children aged 5 – 6 years in Cenpalagi hamlet. This type of research is field research. This type of research uses a qualitative approach, a pedagogic approach, a psychological approach and a sociological approach. This study uses data analysis techniques with the process of reducing data,, presenting data, and drawing concluisions. The results of the study show that there are several roles of the family in providing habituation to children, that is : a) routine habituation b) always consistent in providing habituation, and c) familiarize children from childhood. Factors supporting parents in giving the habit of sorry, pleaseand thank you to children aged 5 – 6 years, namely : a) parental support b) a good environment. While the inhibiting factors are a) the busyness of parents, b) the lack of attention of parents in getting used to children, and c) children’s preferences in playing make parents lack of time for children.